Repurposing Clinic-Tested Drugs to Treat Rare Neurogenetic Diseases by Transcriptional Modulation - Hadwen, Jeremiah (Université d'Ottawa / University of Ottawa, 2018)
Rare diseases caused by single-gene mutations affect almost one million Canadians. According to the Online Mendelian Inheritance in Man database, ~4,500 rare monogenic diseases have a known cause; but less than 5% of patients have access to disease-modifying drugs. The dearth of accessible drugs for patients suffering from rare genetic diseases is partly due to the astronomical costs of traditional drug development which, when combined with the small target population, make rare disease therapeutics unattractive ventures for the pharmaceutical establishment. The paucity of cost-effective treatments for rare diseases has resulted in the promotion of clinic-ready drug repurposing as a tenable strategy for rare disease therapeutics. To identify repurposed candidates for rare neurogenetic diseases, I conducted a transcriptome-wide drug screen in mouse primary cerebrocortical cultures. RNA sequencing was used to develop a database of transcriptome-wide differential expression for 218 clinic-tested drugs. The “Neuron Screen” database was queried to identify drugs that upregulate ~60 rare neurogenetic disease genes (type I hits). Gene set enrichment pathway analysis by Ingenuity Pathway Analysis (IPA) was used to identify network associated drug-gene interactions (type II hits). Both types of drug-gene hits were further assessed in vitro and in vivo by qRT-PCR and western blot analysis. This analysis showed that the IPA-based network-associated approach reduces the false positive rate when identifying differentially expressed genes in transcriptome-wide data-sets. The analysis also identified two drug-gene interactions with genes that cause rare neurogenetic disease, thyroid hormone-Pmp22 and dexamethasone-Mfsd2a, that merit further investigation. This work proves the utility of the Neuron Screen database to connect rare disease genes with transcript-modulating drugs and provides a starting point to understand the transcriptional effects of pharmacologic agents on the mammalian brain.
Keywords: Neurogenetics; Rare diseases; Drug repurposing